Structural and functional support among US older adults with asthma: cross-Sectional associations with medication adherence. Issue 8 (27th August 2019) - O'Conor, Rachel; Hebert-Beirne, Jeni; Kwasny, Mary; Eldeirawi, Kamal; Hasnain-Wynia, Romana; Wisnivesky, Juan; Wolf, Michael; Federman, Alex
Abstract : Objectives: Disadvantaged older adults may benefit from social support in adhering to their medications, but the multidimensional nature of social relationships makes it difficult to identify the most relevant domain. We examined associations of structural and functional support with medication adherence among a cohort of older adults with asthma. Design: Cross-sectional analysis of the Asthma Beliefs and Literacy in the Elderly cohort study. Setting: Outpatient clinics in New York, New York, and Chicago, Illinois, USA. Participants: English-speaking and Spanish-speaking older adults (≥60 years) with asthma. Outcome measures: Medication adherence was measured using dose counts from inhaler and self-report. Results: Among 383 participants, the mean age was 67 years, 38% identified as Hispanic, 33% identified as black, 52% reported monthly incomes ≤US1350 and 64% demonstrated poor adherence to their asthma controller medication. Structural and functional support were weakly correlated (r=−0.15, p=0.005). In adjusted analyses, structural support was not associated with medication adherence. Participants who received infrequent functional support in managing their medications had lower odds of poor adherence according to dose counts (OR 0.51, 95% CI 0.26 to 0.98), but not when assessed via self-report (OR 0.81, 95% CI 0.44 to 1.48). Conclusion: The receipt of frequent functional support in managing medications was associated with poor adherence to asthma controller medications. Further research is needed to better understand the manner and context which functional support operates in relation to medication adherence among older adults.